Use Of Folklore Genres In Kurdısh (Kurmancî) Teachıng Books: Example Of Natıonal Educatıon Books - Kurt, Åžehmus (Humanities Journal of University of Zakho, 2022)
Folklore is used in many areas of education with its different genres. One of the areas in which folklore is used is language teaching. Many folklore genres such as folk tales, fairy tales, folk songs, folk poetry, riddles and rhymes, are also used in Kurdish teaching as teaching materials. Kurdish teaching in Turkey was carried out in independent and private institutions until 2010. In 2012, with a decree of the Turkish Ministry of National Education, Kurdish (Kurmancî/Zazakî) entered the curriculum as an elective course. According to the relevant decision, students in secondary schools (5-8 grades) were able to choose Kurdish as an elective course. If 10 or more students choose Kurdish as an elective course in a school, the school administration is obliged to open the course. A commission was established at Mardin Artuklu University following the request of the ministry in order to prepare the books to be used in the relevant courses. The commission prepared Kurdish teaching books for 5,6,7, and 8th grades, which were used until 2017 when they were deprecated. After the deprecation, a new commission of teachers was assembled from Batman province by the Ministry of National Education. The new commission has prepared Kurdish teaching books to be taught in the same classes. Related books are still used in Elective Kurdish Courses. In this study, the way folklore genres are used in Kurdish teaching is discussed. The aforementioned Kurdish teaching books were examined with the example of 5th grade Kurdish (Kurmancî) books in both sets. Documentation Analysis Method was used in the study. For this purpose, firstly the adventure of Kurdish teaching in Turkey was presented, then a theoretical framework was given regarding language teaching and the use of folklore genres in language teaching. Finally, the books subject to the study were examined in depth and the use of folklore genres in related books was analyzed in terms of quality and quantity.